A conceptual model on reintegration after prison in Norway. Issue 3 (29th August 2019) - Larsen, Bjørn Kjetil; Hean, Sarah; Ødegård, Atle
Abstract : Purpose: Many offenders struggle when attempting to reintegrate into society after release from prison, and the conditions they face after release often lead to reoffending. The purpose of this paper is to present a conceptual model on reintegration after prison. The model has the potential to guide practitioners in their understanding of the relationships between welfare services and the agency of the offender. Design/methodology/approach: The model was developed from a small-scale study in the Norwegian Criminal Justice system, which is well known for its emphasis on rehabilitation and crime prevention. Data collection aimed to explore the reintegration process from the perspective of the hard-to-reach and vulnerable population of serial offenders. Nine prisoners in two different prisons were interviewed. A thematic analysis identified two main themes that related, first, to the personal challenges the offenders faced in the rehabilitation and reintegration process and, second, to the factors in the welfare services that interacted with the prisoners' psychosocial issues in the reintegration process. Findings: Findings suggest that the interaction between the psychosocial needs of the prisoners and the organization of the welfare services is complex and does not harmonize. The findings underpin the argument that the current reintegration strategies for certain groups of inmates need to be questioned and challenged. Research limitations/implications: The model is a conceptual model intended to provide a lens from which to reinterpret offenders' experiences of reintegration and applied to only the small and exploratory study described in this paper. As such, it requires further testing and substantiation, and the model and the study's findings should be regarded as tentative and cannot be generalized to a larger population. The prisoners were selected by the first author for convenience, and it is possible that this also influenced the findings. Other inmates may have presented other experiences. Originality/value: There are few studies looking into reintegration from the reoffenders' perspective, and this study also presents a model that serves as a reflective and analytical tool to developing new approaches to supporting offenders in their reintegration into society from prison in the future.